Safety and tolerability of prescription omega-3 fatty acids: A systematic review and meta-analysis of randomized controlled trials - Chang, Cheng-Ho; Tseng, Ping-Tao; Chen, Nai-Yu; Lin, Pei-Chin; Lin, Pao-Yen; Chang, Jane Pei- Chen; Kuo, Feng-Yu; Lin, Jenshinn; Wu, Ming-Chang; Su, Kuan-Pin (Prostaglandins, leukotrienes and essential fatty acids, 2018)
Omega-3 fatty acids [eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] are widely recommended for health promotion. Over the last decade, prescription omega-3 fatty acid products (RxOME3FAs) have been approved for medical indications. Nonetheless, there is no comprehensive analysis of safety and tolerability of RxOME3FAs so far. A systematic review of randomized controlled trials (RCTs) was carried out based on searches in six electronic databases. The studies involving marketed RxOME3FA products were included, and adverse-effect data were extracted for meta-analysis. Subgroup analysis and meta-regression were conducted to explore the sources of potential heterogeneity. Among the 21 included RCTs (total 24,460 participants; 12,750 from RxOME3FA treatment cohort and 11,710 from control cohort), there was no definite evidence of any RxOME3FA-emerging serious adverse event. Compared with the control group, RxOME3FAs were associated with more treatment-related dysgeusia (fishy taste; p = 0.011) and skin abnormalities (eruption, itching, exanthema, or eczema; p < 0.001). Besides, RxOME3FAs had mild adverse effects upon some non-lipid laboratory measurements [elevated fasting blood sugar (p = 0.005); elevated alanine transaminase (p = 0.022); elevated blood urea nitrogen (p = 0.047); decreased hemoglobin (p = 0.002); decreased hematocrit (p = 0.009)]. Subgroup analysis revealed that EPA/DHA combination products were associated with more treatment-related gastrointestinal adverse events [eructation (belching; p = 0.010); nausea (p = 0.044)] and low-density lipoprotein cholesterol elevation (p = 0.009; difference in means = 4.106mg/dL). RxOME3FAs are generally safe and well tolerated but not free of adverse effects. Post-marketing surveillance and observational studies are still necessary to identify long-term adverse effects and to confirm the safety and tolerability profiles of RxOME3FAs. •Among the 21 included RCTs, there was no definite evidence of any RxOME3FA-emerging serious adverse event.•RxOME3FAs were associated with mild adverse events and minor changes upon laboratory measurements.•The two subgroups of RxOME3FAs,EPA/DHA combinations and EPA-only products, may have slightly different adverse-effect profiles.